Dispute avoidance procedure: observing the influence of legal culture towards a workable legal system - Mohd Danuri, Mohd Suhaimi; Mohd Ishan, Zahira; Mustaffa, Nur Emma; Abd Karim, Saipol Bari; Mohamed, Othman; A. Rahmin, Rabi'atul 'Adawiyah (Universiti Putra Malaysia Press, 2015)
It is pertinent to specifically conduct research on the viability of introducing dispute avoidance procedure (DAP) for construction industry due to the lack of research in this area, as most of the current research covers various issues within dispute resolution procedure and management field. The objective of this study is to examine the future of DAP in the Malaysian construction industry by looking into the perceptions of the construction industry players. Data were collected through interview of selected respondents and analyses to reveal patterns to help formulate a viable DAP mechanism. NVivo software has been used to manage and organise complete interview transcripts and facilitate data analysis process for this study. This study reveals that the existing DAP mechanisms are not viable for the Malaysian construction industry at present, mainly due to the issue of costing. Thus, a modified version of DAP was formulated to promote a viable mechanism. This study suggests that the structural elements of a viable DAP mechanism could be in the form of an 'involvement of top management' from both contracting parties (without the involvement of any third parties) who are decision makers or persons with financial authority, and the process is through 'discussion and negotiation'. In essence, this study captures the legal culture and trade usage of the industry which assisted the formulation of a viable DAP mechanism.